MICRO-COSTING OF THE DIRECT LABOR OF PAID HOME CARE WORKERS: A SINGLE CASE STUDY - Lima, Cátia Correia; Lima, Antônio Fernandes Costa (Cogitare Enfermagem, 2024)
Objective: To calculate the average direct costs related to the labor of a paid home caregiver in carrying out the procedures that make up comprehensive care for a dependent elderly woman. Method: quantitative, exploratory-descriptive micro-costing, in the form of a single case study, with data collected from August to September 2023 in a residence in a municipality in São Paulo, Brazil. Results: the average costs were US$ 0.39 for upper airway aspiration; US$ 1.41 for bed baths, bed-making, and dressing; US$ 0.43 for enteral catheter diet; US$ 0.07 for eye hygiene; US$ 0.13 for oral hygiene; US$ 0.15 for washing hair in bed; US$ 0.08 for enteral catheter medication; US$ 0.07 for decubitus changes; US$ 0.17 for diaper changes. It amounted to US$6.37/day. Conclusion: The contribution of this study is to propose a rational basis for establishing a fair price for procedures that are part of comprehensive care for the dependent elderly, carried out by paid home caregivers.